3(2x-1)-4(x+2)=5(2x+3)-7(x-2)

Simplify each term.

Apply the distributive property.

3(2x)+3⋅-1-4(x+2)=5(2x+3)-7(x-2)

Multiply 2 by 3.

6x+3⋅-1-4(x+2)=5(2x+3)-7(x-2)

Multiply 3 by -1.

6x-3-4(x+2)=5(2x+3)-7(x-2)

Apply the distributive property.

6x-3-4x-4⋅2=5(2x+3)-7(x-2)

Multiply -4 by 2.

6x-3-4x-8=5(2x+3)-7(x-2)

6x-3-4x-8=5(2x+3)-7(x-2)

Simplify by adding terms.

Subtract 4x from 6x.

2x-3-8=5(2x+3)-7(x-2)

Subtract 8 from -3.

2x-11=5(2x+3)-7(x-2)

2x-11=5(2x+3)-7(x-2)

2x-11=5(2x+3)-7(x-2)

Simplify each term.

Apply the distributive property.

2x-11=5(2x)+5⋅3-7(x-2)

Multiply 2 by 5.

2x-11=10x+5⋅3-7(x-2)

Multiply 5 by 3.

2x-11=10x+15-7(x-2)

Apply the distributive property.

2x-11=10x+15-7x-7⋅-2

Multiply -7 by -2.

2x-11=10x+15-7x+14

2x-11=10x+15-7x+14

Simplify by adding terms.

Subtract 7x from 10x.

2x-11=3x+15+14

Add 15 and 14.

2x-11=3x+29

2x-11=3x+29

2x-11=3x+29

Subtract 3x from both sides of the equation.

2x-11-3x=29

Subtract 3x from 2x.

-x-11=29

-x-11=29

Add 11 to both sides of the equation.

-x=29+11

Add 29 and 11.

-x=40

-x=40

Multiply each term in -x=40 by -1.

(-x)⋅-1=40⋅-1

Multiply (-x)⋅-1.

Multiply -1 by -1.

1x=40⋅-1

Multiply x by 1.

x=40⋅-1

x=40⋅-1

Multiply 40 by -1.

x=-40

x=-40

Solve for x 3(2x-1)-4(x+2)=5(2x+3)-7(x-2)